Experiences and attitudes of Setswana speaking teachers in using an indigenous African language on an online assessment platform - Maglin Moodley; Reuben Dlamini (South African Journal of Education, 2021)
Education in the 21st century must have a vision that will support and empower teachers to face the demands of the digital age. The use of information communication technology (ICT) in education can serve this end but ensuring access to digital resources will not address the digital disparity. Culture and language play an equally important role in exacerbating and maintaining the digital disparity as the traditional factor of access. In the study reported on here we investigated the experiences and attitudes of Setswana-speaking teachers in 3 primary schools in the North West province, South Africa, as they were exposed to online software in Setswana, an indigenous African language. Purposive sampling was used to select 7 teachers for the study. Two research questions were answered using systematic self-observation (SSO) instruments, the participant observation (PO) instrument and the in-depth interview (IDI) instrument to determine the experiences and attitudes of the teachers. Thematic analysis was used to analyse the interview data. It was found that accuracy of translation was key for adopting and using software in an African language. The teachers felt that English was the language of ICT and that African languages were not intellectual languages and did not have the capacity to be used in ICT. It is, therefore, recommended that more must be done to translate software into African languages and an effort must be made to raise the status of African languages in academic and technical fields.